Urocortin 3 Levels Are Impaired in Overweight Humans With and Without Type 2 Diabetes and Modulated by Exercise - Kavalakatt, Sina; Khadir, Abdelkrim; Madhu, Dhanya; Hammad, Maha; Devarajan, Sriraman; Abubaker, Jehad; Al-Mulla, Fahd; Tuomilehto, Jaakko; Tiss, Ali (Frontiers in Endocrinology, 2019)
Urocortin3 (UCN3) regulates metabolic functions and is involved in cellular stress response. Although UCN3 is expressed in human adipose tissue, the association of UCN3 with obesity and diabetes remains unclear. This study investigated the effects of Type 2 diabetes (T2D) and increased body weight on the circulatory and subcutaneous adipose tissue (SAT) levels of UCN3 and assessed UCN3 modulation by a regular physical exercise. Normal-weight (n=37) and overweight adults with and without T2D (n=98 and n=107, respectively) were enrolled in the study. A subset of the overweight subjects (n=39 for each group) underwent a supervised 3-month exercise program combining both moderate intensity aerobic exercise and resistance training with treadmill. UCN3 levels in SAT were measured by immunofluorescence and RT-PCR. Circulatory UCN3 in plasma was assessed by ELISA and was correlated with various clinical and metabolic markers. Our data revealed that plasma UCN3 levels decreased in overweight subjects without T2D compared with normal-weight controls [median; 11.99(0.78-86.07) and 6.27(0.64 -77.04), respectively; p<0.001], whereas plasma UCN3 levels increased with concomitant T2D [median; 9.03(0.77-104.92) p<0.001]. UCN3 plasma levels were independently associated with glycemic index; fasting plasma glucose and hemoglobin A1c (r=0.16 and r= 0.20, p<0.05, respectively) and were significantly different between both overweight, with and without T2D, and normal-weight individuals (OR=2.11 [1.84–4.11, 95% CI] and OR=2.12 [1.59–3.10, 95% CI], p<0.01, respectively). Conversely, the UCN3 patterns observed in SAT were opposite to those in circulation; UCN3 levels were significantly increased with body weight and decreased with T2D. After a three-month supervised exercise protocol, UCN3 expression showed a significant reduction in SAT of both overweight groups (2.3 and 1.6-fold change; p<0.01, respectively). In conclusion, UCN levels are differentially dysregulated in obesity in a tissue-dependent manner and can be mitigated by regular moderate physical exercise.